On generalized M-projective curvature tensor of para-Sasakian manifold - Swati Jain; Teerathram Raghuwanshi; Manoj Kumar Pandey; Anil Goyal (Miskolc Mathematical Notes)
The purpose of the present paper is to study some properties of generalized MMZR(X,Y)⋅M~∗∗=0ηM~∗∗(X,Y)⋅S=0ψ=1